The Effects of the Global Crisison Islamic and Conventional Banks : A Comparative Study - Dridi, Jemma (IMF Working Papers; Working Paper, 2010)
This paper examines the performance of Islamic banks (IBs) and conventional banks (CBs) during the recent global crisis by looking at the impact of the crisis on profitability, credit and asset growth, and external ratings in a group of countries where the two types of banks have significant market share. Our analysis suggests that IBs have been affected differently than CBs. Factors related to IBs' business model helped limit the adverse impact on profitability in 2008, while weaknesses in risk management practices in some IBs led to a larger decline in profitability in 2009 compared to CBs. IBs' credit and asset growth performed better than did that of CBs in 2008-09, contributing to financial and economic stability. External rating agencies' re-assessment of IBs' risk was generally more favorable.